The evaluation of the efficacy and safety about apatinib combined with immune checkpoint inhibitors in advanced gastric cancer: a real-world study - Zhu, Peng-Fei; Yang, Liu; Chen, Zhe-Ling (Frontiers in Oncology, 2025)
BackgroundApatinib and immune checkpoint inhibitors (ICIs) have shown promise as third-line treatments for advanced gastric cancer (AGC). This study compared the efficacy and safety of apatinib combined with ICIs versus apatinib monotherapy in AGC patients after second-line treatment failure.MethodsWe conducted a retrospective analysis of 48 AGC patients with postoperative recurrence/metastasis treated at Zhejiang Provincial People’s Hospital between January 2018 and September 2022. Patients received either apatinib plus ICIs (n=23) or apatinib alone (n=25). Primary endpoints were overall survival (OS) and progression-free survival (PFS); Secondary endpoints included safety and subgroup analyses.ResultsWith median follow-up of 4.25 months, the combination group showed significantly longer median OS (6.0 vs 3.0 months, HR=0.44, 95%CI 0.24-0.82, P=0.009) and PFS (3.0 vs 2.0 months, P=0.155). Subgroup analysis revealed patients with liver metastasis receiving combination therapy had superior OS (7.5 vs 4.0 months, P=0.036). The objective response rate was higher with combination therapy (4.3% vs 0%), though not statistically significant (P=0.292). Safety profiles were comparable between groups, with no significant increase in severe adverse events with combination therapy.ConclusionApatinib combined with ICIs demonstrated improved survival outcomes compared to apatinib monotherapy in AGC, particularly for patients with liver metastasis, without increasing severe toxicity.